A Hydrophobic‐Interaction‐Based Mechanism Triggers Docking between the SARS‐CoV‐2 Spike and Angiotensin‐Converting Enzyme 2. Issue 12 (15th October 2020) - Li, Jiacheng; Ma, Xiaoliang; Guo, Shuai; Hou, Chengyu; Shi, Liping; Zhang, Hongchi; Zheng, Bing; Liao, Chenchen; Yang, Lin; Ye, Lin; He, Xiaodong
Abstract: A recent experimental study found that the binding affinity between the cellular receptor human angiotensin‐converting enzyme 2 (ACE2) and receptor‐binding domain (RBD) in the spike (S) protein of novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is more than tenfold higher than that of the original severe acute respiratory syndrome coronavirus (SARS‐CoV). However, main chain structures of the SARS‐CoV‐2 RBD are almost the same with that of the SARS‐CoV RBD. Understanding the physical mechanism responsible for the outstanding affinity between the SARS‐CoV‐2 S and ACE2 is an "urgent challenge" for developing blockers, vaccines, and therapeutic antibodies against the coronavirus disease 2019 (COVID‐19) pandemic. Taking into account the mechanisms of hydrophobic interaction, hydration shell, surface tension, and the shielding effect of water molecules, this study reveals a hydrophobic‐interaction‐based mechanism by means of which SARS‐CoV‐2 S and ACE2 bind together in an aqueous environment. The hydrophobic interaction between the SARS‐CoV‐2 S and ACE2 protein is found to be significantly greater than that between SARS‐CoV S and ACE2. At the docking site, the hydrophobic portions of the hydrophilic side chains of SARS‐CoV‐2 S are found to be involved in the hydrophobic interaction between SARS‐CoV‐2 S and ACE2. Abstract : Understanding the mechanism responsible for the outstanding affinity between the novel severe acute respiratory syndrome coronavirus 2 spike (SARS‐CoV‐2 S) and human angiotensin‐converting enzyme 2 (ACE2) is an "urgent challenge" for developing blockers, vaccines, and therapeutic antibodies against the coronavirus disease (COVID‐19) pandemic. Taking into account the mechanisms of hydrophobic effects and the shielding effects of water molecules, a hydrophobic‐interaction‐based mechanism by means of which SARS‐CoV‐2 S and ACE2 bind together in an aqueous environment is revealed.